Ye. A. Boratynski's Message To Bulgarin: the Author's Editions and Literary Context - Feduta, Aleksandr (Respectus Philologicus, 2003)
In this article literary and everyday life context, which caused different author's versions of Yevgeny Boratynsky's message "To Bulgarin", is analysed. The researcher claims that there is a deliberate enlargement of the addressees of this letter. While the only real addressee of the first edition of the message (1821) is Faddey Bulgarin, in the second edition (1823–1826) the poet abolishes his dedication to Bulgarin because at that time polemic with his another acquaintance and literary opponent Wilhelm Küchelbecker becomes more actual. The third edition of the message (1832–1833) practically has no concrete addressee on account of both non-literary (Küchelbecker was exiled for his participation in the armed insurrection) and literary (polemic with Bulgarin and Küchelbecker have cease to be actual for Boratynsky) reasons. The researcher's arguments are based on comparative analysis of different editions of the message and examinations of texts written by poet's contemporaries.
Keywords: Boratynsky; Baratynsky; Bulgarin; Küchelbecker; reader; addressee; letter